The putative endemic Mexican reef coral Porites baueri Squires 1959 (Scleractinia: Poritidae) is a synonym of the widespread coral Porites lobata Dana 1846 - Medina-Rosas, Pedro; López-Pérez, Andrés; Reyes-Bonilla, Hector (Zootaxa, 2020)
Morphological analysis and microscopic observations of the Porites baueri holotype and specimens of other Porites species from different sites of the Mexican Pacific, allowed confirmation that Porites baueri is subjective synonym of Porites lobata. The holotype of Porites baueri was collected in the Marías Islands in 1957, and described as a new species by Squires in 1959. Since then, this species was considered as endemic, which is due to the lack of other specimens or a review of the taxonomic characters until now. The Mexican Pacific marine fauna loses a valid reef coral species, currently at 34, but gains in taxonomic clarity by ending almost 60 years of controversy.